Stepping onto fertile ground: urban teachers' preparation for interdisciplinary inquiry. (3rd April 2018) - Doerr-Stevens, Candance; Woywod, Christine
ABSTRACT: Contextualized by efforts to support arts integration in one of the largest school districts in the United States, this qualitative study examines the experiences of educators as they participate in various arts-centred forms of professional development. Drawing on the work of, the tenets of arts-centered learning, the authors use Mediated Discourse Analysis and Teachers' Life Histories to account for the social, personal and political processes and activity involved in making meaning and shaping dispositions towards teaching in and through the arts. Findings reveal how arts-centred programming can promote growth in educators' confidence creating curriculum in the arts and collaborating with artists and other teachers, but suggest that embodied practices within interdisciplinary teams and continued coaching are key as educators prepare for guiding students through interdisciplinary inquiry and implementing arts-centred programming. Three fields of emergence for learning within this study include (1) Enactment of Artist-As-Teacher & Teacher-As-Artist (2) Multimodal Inquiry via Group Art-Making; and (3) Collaborative Curriculum Design. These fields of emergence are considered as interdisciplinary traversals, representing educators' movements across disciplinary boundaries and between associated identities.